Evaluate the doses to the Organs At Risk (OAR) calculated by using oncentra treatment planning system for cervical cancer - Azmi, Norazrien Suhaila Nor (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
Objective: The aim of this work was to determine doses to rectum and bladder for dose behaviors in the treatment of cervical cancer by high dose rate (HDR) intracavitary brachytherapy (ICRT) using Ocentra treatment planning system. Materials and methods: A retrospective study was carried out on 1 0 patients with a total of 20 fractions (1 51 and 251 fractions for each patient) of cervical cancer treated with HDR intracavitary brachytherapy in addition to external radiotherapy (EBRT). Brachytherapy treatment planning was performed using Ocentra Treatment Planning System (Nucletron). Before this, the treatment was done using Plato treatment planning. Fletcher-suit applicators (Nucletron) with different size of ovoid which are mini (1.5 mm), small (2.0mm) and medium (2.5mm) are used for ICBT. The prescribed doses 900 cGy (9 Gy) for each fraction is normalised at applicator point. Normal distributions were tested for the rectum and bladder doses for any statistical conclusions. Results: It was observed that rICUR and bICRU were found to show normal distribution for fraction one with mean dose of 38% and 46% and standard deviation of 16% and 17%, respectively. Then rICUR and bICRU for fraction two with mean dose of 35% and 41% and standard deviation of 13% and 1 0 % respectively. Conclusions: The normality behavior of the rectal and bladder point dose show that less than 60% and 80 % of the prescribed dose at point A which means is in the limit of International Commission on Radiation Units (ICRU).